Theaflavin Induces Apoptosis of A375 Human Melanoma Cells and Inhibits Tumor Growth in Xenograft Zebrafishes Through P53- and JNK-Related Mechanism - Zhang, Lei; Yan, Bo; Meng, Shijie; Zhou, Li; Xu, Yiqiao; Du, Wenxi; Shan, Letian (Frontiers in Pharmacology, 2020)
Theaflavin (TF) is a major active pigment and polyphenol of tea, possessing anti-cancer activities. However, little is known about its activity and mechanism against melanoma. To determine whether TF affects melanoma cells, we conducted in vitro assays of cell viability, morphology observation, DAPI staining, and flow cytometry as well as in vivo experiment by using a xenograft model of larval zebrafishes. Real-time PCR (qPCR) and Western blot (WB) analyses were conducted to explore the mechanism of TF. The in vivo data showed that TF from 50 to 400 μg/ml exerted significant anti-proliferative effect on A375 cells in a dose-dependent manner, with IC50 values ranging from 218.9 to 84.9 μg/ml for 24 to 72 h. It also induced early and late apoptosis of A375 cells in a dose-dependent manner. In vivo, TF significantly inhibited A375 tumor growth in larval zebrafishes at 0.67 and 2.0 μg/ml. qPCR and WB data showed that TF significantly activated proteins in P53 pathway (ATM, CHK1/2, P53, and CASP8/3) and JNK pathway (ASK1, JNK, C-JUN) through phosphorylation and cleavage, followed by activation of pro-apoptotic molecules (PARP, BAX, BIM, PUMA, and P53). In sum, TF possessed anti-proliferative, pro-apoptotic and tumor-inhibitory effects on A375 cells through a mechanism associated with P53 and JNK pathways. This is the first report on TF regarding its anti-melanoma activity, making it a promising candidate of natural products for clinical treatment of melanoma.